The impact of female chief executive officers, ownership, and globalization on ASEAN manufacturers' technical efficiency performance - Yot Amornkitvikai; Teerawat Charoenrat (Research in Globalization, 2024)
The premature deindustrialization of Association of Southeast Asian Nations(ASEAN) economies has impeded their development by restricting all prospects for growth, including economies of scale, human capital development, and worker productivity. In male-dominated industries, sexism and discrimination may prevent women from attaining leadership positions, especially in manufacturing. This is especially apparent where women are viewed as less technical in ASEAN manufacturing. Therefore, this study employs the beta regression model to examine the impact of female CEOs and those with ownership on the technical efficiency and performance of ASEAN manufacturers. The impact of economic globalization via foreign direct investment (FDI) and exports on technical efficiency is also examined in this study. FDIs are found to enhance ASEAN manufacturers' technical efficiency. This study also found that firms operated by female CEOs are more technically efficient, implying that they prefer stewardship-driven management strategies over agency-driven approaches. Female CEOs with ownership are likely to decrease technical efficiency, confirming the entrenchment hypothesis that their interests are not aligned with shareholders' interests. In addition, skilled labor, ISO certification, IT use, and firm size boost their technical efficiency.
Keywords: 330; female CEOs; Globalization; Manufacturing; Ownership; Technical efficiency